SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SUPERVISOR TERBAIK PADA BAGIAN PERENCANAAN PT. PLN (PERSERO) AREA MEDAN MENERAPKAN PREFERENCE SELECTION INDEX - Mesran, Mesran; Huda, Nurul; Hutagalung, Siti Nurhabibah; Khasanah, Khasanah; Iskandar, Akbar (STMIK Budi Darma, 2018)
Every company carries out functions contained in management, the company must have a well-defined plan. The existence of a plan in a company is very influential on the performance process in the period of dependence to obtain good management results, therefore managers in the company must be able to master the whole of the existing management functions.Problems faced by PT. PLN (Persero) The current Medan Area is the absence of a supervisor selection program that uses measurements based on aspects and criteria that are absolutely set by the company. However, with the many criteria needed to become a supervisor, decision makers must be observant in choosing prospective replacement supervisors who will fill supervisor positions in their companies.The Preference Selection Index method generates a ranking of the selection of an object with the success of the best index up to poor. This method is useful when there are conflicts in determining the relative importance between attributes. In the PSI method, the results are obtained with minimal and simple calculations as they are based on statistical concepts without the need for attribute weights. With proper consideration, this method can be one of the tools for specific selection in decision-making systems, especially the selection of the best planning supervisors. The choice of the best supervisor planning taken as a basis for decision making, must use criteria that can be defined clearly and objectivelyKeywords: Supervisor, Decision, Planning